Metallurgical Characterisation Comparing Recycled and Ore-based Steels for Automotive Crankshafts - Pautzke, Joshua Michael (My University, 2020)
Steel crankshafts are a substantial component in internal combustion engines. A critical feature of crankshafts is their bearing surfaces which have to meet tight requirements regarding hardness and compressive residual stresses in order for the component to function properly. The properties of the bearing surfaces are to a large extent determined by a grinding operation which is used as the final step in the manufacturing chain. In practice, it is commonly experienced that there are batch-to-batch material variations which can cause grindability issues leading to unwanted high scrap rates when the surface requirements are not met. These issues are especially pronounced when both steels made from recycled resources and from iron-ore are fed into the production line. The underlying reasons for these grindability variations are largely unknown. The present master thesis project addresses metallurgical differences between a recycled and an iron-ore based steel batch and investigates potential effects on the grindability. Both steel bars (as supplied by steel mills) and the final ground crankshafts are examined. Samples taken from different positions of the crankshaft were investigated using optical and scanning electron microscopy, Vickers hardness testing, Barkhausen noise analysis and XRD residual stress measurements. The results show that there is a significant difference in grain size between the microstructure of the recycled and ore-based initial, as received steel bars. However, metallurgical examination of the unhardened material of the corresponding crankshaft material indicates that these grain size differences have largely been eliminated during the processing steps. When considering the crankshafts, the recycled steel batch is clearly more inhomogeneous but also has a clearly higher hardenability, while the hardness close to the bearing surface only shows insignificant differences. The estimated prior austenite grain sizes and residual stresses seem to differ more within different spots in a material than between recycled and ore-based material.
Keywords: Crankshaft; steel; recycled; one-based; grindability; Microstructure